Oliver twist - Dickens, Charles; Charles Dickens; Penguin Books (London : Penguin Books, 2020)
Oliver Twist's parents are dead and he grows up in the workhouse, where life is very hard. One day Oliver runs away to London. There, he enters a life of crime with the old man Fagin, the Artful Dodger, frightening Bill Sykes and kind-hearted Nancy. How will Oliver live in this dangerous world? Penguin Readers is a graded reading series for English Language Teaching (ELT) markets, designed for teenagers and young adults learning English as a foreign or second language. Level 6 Readers, are B1+ in the CEFR framework. The longer text is made up of sentences with up to four clauses, introducing future continuous, reported questions, third conditional, was going to and ellipsis
The book describe the story of an orphan boy. Oliver Twist's parents are dead and he grows up in the workhouse, where life is very hard. One day Oliver runs away to London. The book is having CD in book
Keywords: Anglais (Langue) Lectures et morceaux choisis pour adultes